A review on safety practices at construction site - Abdul Razak, Nadeera; Tan, Chin Keng (2012)
Over the years, the scenario of the construction industry has become more challenging since the development of the rapid growth of this sector. In relation to that, safety issues have become a center of attraction in the construction industry. This paper reviews the safety practices at construction sites. Based on the review, there are ten safety practices found, i.e, safety policy, education and training, safety inspection and safety auditing, safety meeting, supervision, pink tickets, red and green zone demarcation, personal protective equipment (PPE), emergency support and safety measuring device and fall protection systems.